A Configuration Management System for Software Product Lines - (:unkn) unknown (My University, 2012)
Software product line engineering (SPLE) is a methodology for developing a family of software products in a particular domain by systematic reuse of shared code in order to improve product quality and reduce development time and cost. Currently, there are no software configuration management (SCM) tools that support software product line evolution. Conventional SCM tools are designed to support single product development. The use of conventional SCM tools forces developers to treat a software product line as a single software project by introducing new programming language constructs or using conditional compilation. We propose a research conguration management prototype called Molhado SPL that is designed specifically to support the evolution of software product lines. Molhado SPL addresses the evolution problem at the configuration level instead of at the code level. We studied the type of operations needed to support the evolution of software product lines and proposed a versioning model and eight cases of change propagation. Molhado SPL supports independent evolution of core assets and products, the sharing of code and the tracking relationships between products and shared code, and the eight cases of change propagation. The Molhado SPL consists of four layers with each layer providing a different type of service. At the heart of Molhado SPL are the versioning model, component object, shared component object, and project objects that allow for independent evolution of products and shared artifacts, for sharing, and for supporting change propagation. Furthermore,they allow product specific changes to shared code without interfering with the core asset that is shared. Products can also introduce product specific assets that only exist in that product. In order to for Molhado SPL to support product line, we implemented XML merging, feature model editing and debugging, and version-aware XML documents. To support merging of XML documents, we implemented a 3-way XML document merging algorithm that uses versioned data structures, change detection, and node identity. To support software product line derivation or modeling of software product line, we implemented support for feature model including editing and debugging. Finally, we created the version-aware XML document framework to support collaborative editing of XML documents without requiring a version repository. The version history is embedded in the documents using XML namespaces, so that the documents remain valid under the XML specification. The version-aware XML framework can also be used to support the exporting of documents from Molhado SPL repository to be edit outside and import back the change history made to the document. We evaluated Molhado SPL with two product lines: a document product line and a the graph data structures product line. This evaluation showed that Molhado SPL supports independently evolution of products and core assets and the eight change propagation cases. We did not evaluate MolhadoSPL in terms of scalability or usability. The main contributions of this dissertation research are: 1) Molhado SPL that supports the evolution of product lines, 2) a fast 3-way XML merge algorithm, 3) a version-aware XML document framework, and 4) a feature model editor and debugger.
Keywords: Feature model; software configuration management; software engineering; software product line; versioning; XML merging